Pemahaman Jihad menurut Qurais Shihab - Kusuma, Wira Hadi (JURNAL ILMIAH SYI'AR, 2016)
Concept of jihad in religious texts in view of Quraish Shihab, and want to know the implications of the missionary movement and understanding in society. often small difference in terms of religion release the horses of war (war) and justify mass genocide, which ironically in the name of god and religion sacred calling. Among the fundamental drivers of violence (violence action) are the respective religions have an understanding tendency toward exclusivism and intolerance. This study to know the concept of jihad in religious texts, in view of Quraish Shihab, and want to know the implications of the missionary movement and understanding in society. Often small differences in terms of religion release the horses of war (war) and justify mass genocide, the which ironically in the name of god and religion sacred calling. Among the fundamental drivers of violence (violence action) are the respective have an understanding tendency toward exclusivism and intolerance.